Risk Factors for Asphyxia in Newborns Systematic Review of Neonatal Health - Ernawati Ernawati; Eko Winarti; Yeni Lutfiana Novita Agnes; Ns. Kun IkaÂ NurÂ R (Syntax Literate, 2023)
Neonatal mortality is still an important global problem. According to WHO (2010), asphyxia causes neonatal mortality between 8-35% in developed countries and 31-56.5% in developing countries. Every year, approximately 3% (3.6 million) of the 120 million newborns experience asphyxia, almost 1 million of these babies die and the incidence of asphyxia neonatorum in Indonesia is approximately 40/1000 live births. This study is a systematic review of 10 studies conducted in 2014-2022 which aims to look at the risk factors for the incidence of asphyxia in newborns in several regions in Indonesia. Most of the research using literature comes from books, health materials, and published journals. The measuring instruments used in these 10 studies were observation sheets and journal entries. The factors studied were risk factors for the incidence of asphyxia according to the mother, the condition of the baby, and labor factors. The results of the review showed that the most studied factors were maternal age, hypertension/preeclampsia, infant age (premature), low birth weight (LBW), and premature rupture of membranes (PROM) with ORs of 3.57; 1.93; 7.49; 9.71; 24.18 which are all significant.